2018
DOI: 10.3928/01484834-20180921-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Methods of Teaching Culture to Bachelor of Science in Nursing Students

Abstract: Background: The nursing literature examining effective methods to teach transcultural self-efficacy demonstrates inconsistent findings. This study evaluated the effectiveness of a nursing stand-alone culture course with concurrent field experiences compared with the standard integrated culture content in the curriculum in increasing transcultural self-efficacy in nursing students. Method: This quasi-experimental, static-group comparison u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The findings of Stiles et al (2018) indicated that an ELNCC was beneficial in developing nursing students’ TSE immediately following the course. This study followed the same experimental group of students through program exit.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The findings of Stiles et al (2018) indicated that an ELNCC was beneficial in developing nursing students’ TSE immediately following the course. This study followed the same experimental group of students through program exit.…”
Section: Discussionmentioning
confidence: 93%
“…In both the control and experimental groups, the students' levels of CC and CAS decreased over time; however, those students who took the course maintained significantly higher CC and CAS levels over time than students who did not take the course, indicating that some long-term benefits were achieved (Lin et al, 2015). Stiles et al (2018) examined the immediate effects of an entry-level nursing culture course (ELNCC) with practical experiences on student's TSE. They used a pretest-posttest design and administered Jeffreys's TSET to first-semester nursing students at the start of the ELNCC and then again at the end of the course.…”
mentioning
confidence: 99%
See 3 more Smart Citations